2019
DOI: 10.3171/2019.3.spine181127
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical investigation of the sacroiliac joint in the setting of lumbosacral fusion: impact of pelvic fixation versus sacroiliac joint fixation

Abstract: OBJECTIVEThe sacroiliac joint (SIJ) is a known source of low-back pain. Randomized clinical trials support sacroiliac fusion over conservative management for SIJ dysfunction. Clinical studies suggest that SIJ degeneration occurs in the setting of lumbosacral fusions. However, there are few biomechanical studies to provide a good understanding of the effect of lumbosacral fusion on the SIJ. In the present study, researchers performed a biomechanical investigation to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…21,22 Finally, biomechanical data indicate that long-segment fusion to S1 may predispose to adjacent segment changes in the SIJ. 23 Outcomes After SIJ Fusion Improvement of lower extremity complaints related to SIJ dysfunction has been reported in previous clinical series for both medical and surgical cohorts. 4,15 Nonsurgical therapy for SIJ-related leg pain has also been shown to be successful in an RCT.…”
Section: Sij and Concomitant Lumbosacral Diseasementioning
confidence: 67%
“…21,22 Finally, biomechanical data indicate that long-segment fusion to S1 may predispose to adjacent segment changes in the SIJ. 23 Outcomes After SIJ Fusion Improvement of lower extremity complaints related to SIJ dysfunction has been reported in previous clinical series for both medical and surgical cohorts. 4,15 Nonsurgical therapy for SIJ-related leg pain has also been shown to be successful in an RCT.…”
Section: Sij and Concomitant Lumbosacral Diseasementioning
confidence: 67%
“…Additional studies on intact SIJ kinematics reported translations along the 3-dimensional coordinate axes on the order of 0.1 mm to 1.04 mm with corresponding rotations of 0.11 to 1.14 degrees. 16 , 91 , 92 …”
Section: Resultsmentioning
confidence: 99%
“…Multidirectional flexibility testing is typically performed along 3 predominant loading axes-flexionextension, lateral bending, and axial rotation under controlled displacement rates of 1 to 3 degrees per second for multiple cycles. To this end, a series of laboratory investigations using the NDI Certus and Vicon MX13 camera systems (Vicon Motion Systems Ltd., Oxford, UK) reported the peak limits of optoelectronic accuracy when evaluating kinematics of the osteoligamentous spine [13][14][15][16][17][18][19][86][87][88][89][90][91][92] (Figure 5A and B).…”
Section: Application Accuracy-musculoskeletal Kinematics Laboratory P...mentioning
confidence: 99%
See 2 more Smart Citations